2022
DOI: 10.1101/2022.05.24.22275529
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depressive and anxiety symptoms during the COVID-19 pandemic: A two-year follow-up

Abstract: Background: There has been much research into the mental health impact of the COVID-19 pandemic and how it is related to time-invariant individual characteristics (e.g. age and gender). However, there is still a lack of research showing long-term trajectories of mental health across different stages of the pandemic. And little is known regarding the longitudinal association of time-varying contextual and individual factors (e.g. COVID-19 policy response and pandemic intensity) with mental health outcomes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…For the categorization of variables, a likelihood test was used, as proposed by Bu et al ( 37 ), using a proportion of 0.5. Variables were included in the adjusted model regardless of the p -value of the crude analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For the categorization of variables, a likelihood test was used, as proposed by Bu et al ( 37 ), using a proportion of 0.5. Variables were included in the adjusted model regardless of the p -value of the crude analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, by May 2020 as many as 29% of participants reported experiencing physiological symptoms of anxiety such as sickness and trembles when they thought about COVID-19 (8). Stress levels regarding catching COVID-19 and becoming ill across the pandemic corresponded with depression and anxiety levels, suggesting that fear of the disease itself influenced mental health (6). However, both our qualitative and quantitative work demonstrated that as people became used to the virus being around and began receiving vaccinations, these stress levels decreased and their relationship to depression and anxiety levels became weaker (6) (9).…”
Section: What Drove Changes In Mental Health?mentioning
confidence: 90%
“…This fluctuation in mental health continued over the second year of the pandemic, with higher levels of depression and anxiety corresponding with an increase in COVID-19 cases and more social distancing restrictions, and lower levels corresponding with fewer restrictions and lower virus levels (6).…”
Section: How Did Mental Health Change Over the Pandemic?mentioning
confidence: 99%
See 2 more Smart Citations